1999
DOI: 10.1021/jp990480k
|View full text |Cite
|
Sign up to set email alerts
|

A New Phase of Hydroquinone and Its Thermodynamic Properties

Abstract: Hydroquinone crystals have been found to undergo first-order phase transition to a denser polymorph with an enthalpy increment, as does resorcinol. The phase stable at room temperature (called R) transforms to the new phase (designated δ) only under elevated pressures. P-V-T relations of the new phase have been measured, and characteristics of the transitions and the triple point among the R phase, the δ phase, and the liquid have been estimated from the thermodynamic consistency. The thermal expansion coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 25 publications
(43 reference statements)
0
29
0
Order By: Relevance
“…During isothermal pressurization in a diamond anvil cell at room temperature, they observed changes in the Raman spectra suggesting two transitions at 3.3 GPa and 12 GPa, respectively. The 3.3 GPa feature was attributed to a new phase, but considering the results of Naoki et al [42], it may correspond to the α to δ transition, which they observed at lower pressures and high temperatures. [44] found that the 3.3 GPa transition was reversible upon pressure decrease, but with a significant pressure hysteresis, and the ambient pressure phase was recovered below 1.3 GPa.…”
Section: Transition Behaviour and Thermal Properties Under Pressure Hmentioning
confidence: 83%
See 3 more Smart Citations
“…During isothermal pressurization in a diamond anvil cell at room temperature, they observed changes in the Raman spectra suggesting two transitions at 3.3 GPa and 12 GPa, respectively. The 3.3 GPa feature was attributed to a new phase, but considering the results of Naoki et al [42], it may correspond to the α to δ transition, which they observed at lower pressures and high temperatures. [44] found that the 3.3 GPa transition was reversible upon pressure decrease, but with a significant pressure hysteresis, and the ambient pressure phase was recovered below 1.3 GPa.…”
Section: Transition Behaviour and Thermal Properties Under Pressure Hmentioning
confidence: 83%
“…Yet another form of HQ, the δ-form, has been detected at elevated temperatures and pressures by Naoki et al [42]. In their differential thermal analysis (DTA) and volume measurements, they observed an endothermic transition from the α-form to a slightly denser phase (1.355 g cm -3 at 443.3 K and 78.5 MPa) on isobaric heating above 0.03 GPa.…”
Section: Transition Behaviour and Thermal Properties Under Pressure Hmentioning
confidence: 95%
See 2 more Smart Citations
“…Hydroquinone is an example of an inclusion compound which 55 exhibits a different crystal form under pressures exceeding ~20MPa. 42 At ambient pressure and temperature, hydroquinone has three forms: the clathrate-forming α and β and a more densely packed form, γ, which is accessible only via sublimation. The β and γ forms both spontaneously transform to the α form, 60 the most stable phase at room temperature.…”
mentioning
confidence: 99%